FOOD HABITS OF THE YELLOW RASBORA, Rasbora lateristriata, (FAMILY: CYPRINIDAE) BROODFISH DURING MOVING TO SPAWNING GROUND - Djumanto Djumanto; F. Setyawan (Universitas Gadjah Mada, 2009)
The purpose of this research was to clarify the food habits of yellow rasbora (Rasbora Iateristiata) when moving into spawning site during spawning season. Specimens of yellow rasbora were collected between July and August, 2007 from spawning site surveys during spawning season in their natural environment which run yearly from April to August. There were 628 individual fish collected from spawning ground, and 30 of them were selected to analyze the gut content. Samples were preserved in alcohol solvent until identified their gut content in laboratory.The results showed that yellow rasbora broodfish fed plankton continuously both in the day and night while moving into the spawning site. Percent Index of Relative Importance values indicated the most important prey items of yellow rasbora were phytoplankton (68.43%), and then zooplankton (29.79%), leaf cut (0.02%), little caterpillar (0.01%), insect larva (0.15%), and unidentified items (1.60%), respectively. Chrysophyta and protozoa was found the most dominant of phytoplankton and zooplankton in the gut content, respectively. Based to the ratio between gut length and total length, and the feeding mode, R. lareritriata is categorized to an omnivorous feeder.